2021
DOI: 10.1186/s13054-020-03438-9
|View full text |Cite
|
Sign up to set email alerts
|

Mortality in septic patients treated with vitamin C: a systematic meta-analysis

Abstract: Background Supplementation of vitamin C in septic patients remains controversial despite eight large clinical trials published only in 2020. We aimed to evaluate the evidence on potential effects of vitamin C treatment on mortality in adult septic patients. Methods Data search included PubMed, Web of Science, and the Cochrane Library. A meta-analysis of eligible peer-reviewed studies was performed in accordance with the PRISMA statement. Only studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
63
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(68 citation statements)
references
References 54 publications
2
63
0
1
Order By: Relevance
“…Meanwhile, different meta-analyses have been conducted on vitamin C in sepsis and critically ill patients. The results are controversial; while some see a reduction in mortality, a shorter hospital stay and/or a reduced need for vasopressors, these effects are not confirmed in other analyses [ 65 , 66 ]. Of note is a meta-analysis that sees effects depending on the chosen vitamin C dose [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, different meta-analyses have been conducted on vitamin C in sepsis and critically ill patients. The results are controversial; while some see a reduction in mortality, a shorter hospital stay and/or a reduced need for vasopressors, these effects are not confirmed in other analyses [ 65 , 66 ]. Of note is a meta-analysis that sees effects depending on the chosen vitamin C dose [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recently published meta-analysis on mortality performed subgroup analyses and found a beneficial effect of vitamin C on short-term mortality (< 30 days). Additionally, survival was improved by a treatment duration of 3-4 days [13]. The results of vitamin C alone versus combination therapy were not different.…”
Section: Introductionmentioning
confidence: 91%
“…In the ACTS trial, the combination therapy did not result in a statistically signi cant reduction in the SOFA score during the rst 72 hours after enrollment and the 30-day mortality [12]. However, the subsequent meta-analysis showed that vitamin C alone or in combination with hydrocortisone/thiamine (treatment 3 to 4 days) reduces the 30-day mortality in patients with septic shock [5]. The heterogeneity of these results may be related to the differences in the e cacy of the combination therapy for different septic shock subtypes.…”
Section: Discussionmentioning
confidence: 98%
“…However, this study has some shortcomings, such as the small sample size and before-after study design. Since the publication of this study, the use of combination therapy has increased gradually [4], and numerous studies have begun to explore the effect of combination therapy on the prognosis of septic shock patients [5][6][7][8][9][10][11][12][13][14]. But these studies have produced inconsistent results and a lack of mechanistic research.…”
Section: Introductionmentioning
confidence: 99%